Teachers’ Proffesional in Integrating Material of Semangko Faulth and Megatrush Mentawai in Learning Geography at Senior High School in Indonesia - Ilham, Muhammad (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The purpose of this research was to describe and analysis of teachers’ professional in integrating material of semangko faulth and megatrush Mentawai in learning geography. This research was a descriptive qualitative research. The data collection techniques used were observation, interviews, and documentation. The informants in this study were teachers of the geography of SMA Negeri 1 Ampek Angkek Kabupaten Agam as much as 2 teachers. Data analysis used reduction, data presentation, and conclusion. The results showed that: professional level of teachers in the integration materials of Faulth Semangko and Megatrush Mentawai in geography learning was 71.56% with the two categories, the ability to plan the organization in the integration of the material Semangko Faulth and Megatrush Mentawai. Teachers were not maximized although this integration was submitted by adjusting the conditions and situations that occur in the environment. The master plan of Teaching and Learning Activity Management that with reference to the achievement of competence and select and prepare appropriate learning procedure (steps teach) in accordance with the curriculum guide device. Teachers have to maximize its ability to plan classroom management and observes the conditions and situation of student learning in the opening stage, the core activity, closing activities, and assessment. Teachers also plan the use of media and learning resources were better at each of meetings. Teachers plan an assessment of student achievement in geography on human and environmental materials as a result of the dynamics of the lithosphere.